2018
DOI: 10.1371/journal.pone.0189327
|View full text |Cite
|
Sign up to set email alerts
|

Social sensing of floods in the UK

Abstract: “Social sensing” is a form of crowd-sourcing that involves systematic analysis of digital communications to detect real-world events. Here we consider the use of social sensing for observing natural hazards. In particular, we present a case study that uses data from a popular social media platform (Twitter) to detect and locate flood events in the UK. In order to improve data quality we apply a number of filters (timezone, simple text filters and a naive Bayes ‘relevance’ filter) to the data. We then use place… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 15 publications
0
88
0
1
Order By: Relevance
“…This study uses a hybrid approach of methods from previous studies which successfully collected and found useful meaning from Twitter data relating to weather events or natural hazards (Lachlan et al ., ; Arthur et al ., ; Cowie et al ., ; Halse et al ., ). Social media data were collected, filtered for relevance and geo‐located.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study uses a hybrid approach of methods from previous studies which successfully collected and found useful meaning from Twitter data relating to weather events or natural hazards (Lachlan et al ., ; Arthur et al ., ; Cowie et al ., ; Halse et al ., ). Social media data were collected, filtered for relevance and geo‐located.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…Using the methods outlined by Arthur et al . (), tweets relating to named storms and storm‐associated weather conditions were collected using the Twitter Streaming API (via a Python script using the Twython package [McGrath, ]). This API returns all tweets up to a limit of 1% of the total volume of tweets at any point in time.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies (Arthur, Boulton, Shotton, & Williams, 2018;Li, Wang, Emrich, & Guo, 2018;Long, Wang, Chen, Jin, & Yu, 2011) have highlighted the importance and applications of social sensing in detecting relevant events and understanding the situation for disaster response and recovery. Social sensing is a technique for collecting and analyzing social posts that deliver online users' observations and sentiments regarding their physical environment.…”
Section: Introductionmentioning
confidence: 99%